2020
DOI: 10.1002/jum.15319
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Fetal Anatomy Ultrasound Assessment Based on Maternal Body Mass Index Does Not Reduce the Rate of Inadequate Visualization

Abstract: Objectives-To determine whether delay of initial anatomy ultrasound based on the maternal body mass index (BMI) reduces the rate of inadequate visualization compared to standard timing at 18 0/7 to 19 6/7 weeks. Methods-A retrospective study of singleton anatomy assessments was conducted at a tertiary care center in the 2-year period before (A, 2012-2014) and after (B, 2014-2016) protocol initiation. Assessments in period B were scheduled on the basis of the BMI in the first trimester: lower than 25 kg/m 2 , 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In the 2000s and 2010s, there was significant literature showing that slightly later gestational age (eg, 22–24 weeks) impacts completion rate of the initial evaluation of anatomy in this population 21,22 . However, possibly related to improvements with imaging technology, this is now doubted by some, 23 and some advocate imaging in the first trimester or very early second trimester to aid completion of fetal anatomy 24,25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2000s and 2010s, there was significant literature showing that slightly later gestational age (eg, 22–24 weeks) impacts completion rate of the initial evaluation of anatomy in this population 21,22 . However, possibly related to improvements with imaging technology, this is now doubted by some, 23 and some advocate imaging in the first trimester or very early second trimester to aid completion of fetal anatomy 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…In the 2000s and 2010s, there was significant literature showing that slightly later gestational age (eg, 22-24 weeks) impacts completion rate of the initial evaluation of anatomy in this population. 21,22 However, possibly related to improvements with imaging technology, this is now doubted by some, 23 and some advocate imaging in the first trimester or very early second trimester to aid completion of fetal anatomy. 24,25 Research Implications This study demonstrated the need for many follow-up ultrasounds in hundreds of patients; the impact of these additional imaging studies on cost of pregnancy care is not estimated in this study, nor is time spent scanning or impact on sonographers.…”
Section: Main Findingsmentioning
confidence: 99%